LEGAL POLITICS OF DEVELOPMENT AND INDUSTRIAL EMPOWERMENT LAW IN INDONESIA - Ahmad Ahmad (NOMOI Law Review, 2020)
Industrialization is an economic activity that processes raw materials or utilizes industrial resources to produce goods that have high values or benefits to the community and include industrial services. Industrial Law regulates all industrial activities that provide protection, guarantees and benefits for industrial activities by regulating the direction of development policies and industrial empowerment in realizing the greatest prosperity for the community. The research method used in this study was normative legal research with a descriptive analysis approach. The results showed that industrial law aimed at forming a just and prosperous national economic structure through setting the direction of development policies and empowering industries in the small and medium industry, green industries, strategic industries, and the use of domestic products and international cooperation.